(untitled) (Journal of Hama University, 2020)
This study aims to know the morphological and biochemical values of Awasi sheep infected by Babesia and it confirms the diagnosis through the tests of blood and the efficiency of the liver during infection.This study was carried out on /33/ infected animal and /30/ control animals, and it has shown there were increasing of heart beats, respiration of breathing, and body temperature. Laboratory study has shown significant decrease values for : RBCs, Hb, PCV, MCV, MCHC, T. Pro., Albumin and Globulin. And it has shown significant increase in ESR, WBCs, AST, ALT, and lymphocyte.The previous results show the extent of liver and blood damage and they confirm the diagnosis through these values